Religiosity and Consumer Acceptance of the Use of Islamic Digital Banking Services in Indonesia: An Extension of the UTAUT Model - Muttaqin, Ibnu (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2024)
The banking world responds to the concept of SDG's with the concept of Green Banking. The implementation of Green Banking is a demand of the current era, one of which is by implementing Digital Banking, both Digital Services and Digital Banks that have begun to exist in Indonesia. Measurement of digital service acceptance can refer to UTAUT theory, in Islamic banking it is suspected that religiosity contributes to the behaviour of digital service users. This research was conducted using quantitative descriptive techniques. Data was taken by distributing questionnaires obtained 186 respondents. The results show that performance expectations, business expectations, and facility conditions have no significant effect on interest in using, while social influence variables, interest in using, and religiosity are proven to have an effect with a positive coefficient direction. The results of the study recommend that companies focus on marketing strategies by utilizing social influence in the community and continue to increase public interest through promotions and other marketing activities. The religiosity side of customers also needs to be considered considering that it has a contribution to the behaviour of using digital services of Islamic banks in Indonesia.